Lingual orthodontics: a review of its history - Poon Kah Chai; Taverne Aart A.R (Sciendo, 1998)
When lingual orthodontics was first introduced about twenty years ago same called it the 'ultimate aesthetic appliance'. Patients and practitioners embraced this new treatment alternative with high expectations. Reports of disappointing results and high costs dampened much of the initial excitement and enthusiasm gradually waned. By the late 1980s, the number of practitioners using the technique had fallen sharply, leaving only a handful who still believed in its potential. Relatively little has been written on lingual orthodontics, almost nothing in recent years. This article takes an objective view of its present status.